The method and index of sustainability assessment of infrastructure projects based on system dynamics in China - Jun Zhou; Yingjia Liu (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: As one of the most important overhead capital of urban economics and social development, the sustainable development of urban infrastructure is becoming a key issue of prosperous society growing. The purpose of this paper is to establish a basic model to analysis certain infrastructure project's sustainable construction and operation. Design/methodology/approach: System dynamics is an effective stimulation method and tool to deal with such complex, dynamics, nonlinear systems, which could be used in analyzing and evaluating all aspects of infrastructure sustainability internally and externally. In this paper, the system is divided into four subsystems and 12 main impact indicators. Through setting the boundary and other basic hypothesis, this paper designs the basic causal loop diagrams and stock & flow diagrams to describe the relationship between variables and establish a quantifiable structure for the system.Findings: Adopting a sewerage treatment in China as a case to test our model, we could conclude that the model of internal sustainable subsystem is reasonable. However, this model is a basic model, and it need to be specific designed for the certain project due to the diversity of infrastructure types and the unique conditions of each projects. Originality/value: System Dynamics (SD) is widely used in the study of sustainable development and has plentiful research achievements from macro perspective but few studies in the microcosmic project systems. This paper focuses on the unique characteristics of urban infrastructure in China and selects infrastructure project which is based on micro-system discussion. The model we designed has certain practical significance in policy setting, operation monitoring and adjustment of the urban projects with high rationality and accuracy.
Keywords: 650; project evaluation; sustainability; urban infrastructure; sustainable development; system dynamics; method; model; indicators; subsystems